Fabrication of high sensitivity 3D nanoSQUIDs based on a focused ion beam sculpting technique. (10th August 2016) - De Leo, Natascia; Fretto, Matteo; Lacquaniti, Vincenzo; Granata, Carmine; Vettoliere, Antonio
Abstract: In this paper a nanofabrication process, based on a focused ion beam (FIB) nanosculpting technique, for high sensitivity three-dimensional nanoscale superconducting quantum interference devices (nanoSQUIDs) is reported. The crucial steps of the fabrication process are described, as are some peculiar features of the superconductor–normal metal–insulator–superconductor (SNIS) Josephson junctions, which may useful for applications in cryocooler systems. This fabrication procedure is employed to fabricate sandwich nanojunctions and high sensitivity nanoSQUIDs. Specifically, the superconductive nanosensors have a rectangular loop of 1 × 0.2–0.4 μ m 2 interrupted by two square Nb/Al–AlO x /Nb SNIS Josephson junctions with side lengths of 0.3 μ m. The characterization of a typical nanoSQUID has been carried out and a spectral density of magnetic flux noise as low as 0.8 μ Φ0 Hz –1/2 has been measured.